Reuse of marble wastes as reinforcement phase in LM6 aluminium matrix composites for automotive applications - Fuhaid, Mutlag S.; Murali, R.V.; Maleque, Md Abdul; Abd Rahman, Mohamed (Inderscience Publishers, 2021)
Reuse of waste materials as reinforcement phase in metal matrix composites is considered as one of the key areas of research due to many advantages such as cost reduction due to abundant availability of the waste materials, unchanged strength of the resulting composites and no special process required for producing composites. In Oman, it is reported that around 100-ton marble wastes are dumped as landfills/day. Waste management is at infancy in Oman which prompts a need to explore alternate applications for landfilled wastes. This paper experimentally verifies the use of marble wastes in making LM6 aluminium matrix composites (AMC) with the help of particle characterisation, elemental analysis and mechanical testing. The results demonstrated an increase of 27% in tensile strength and a two-fold increase in hardness value of composites developed with 5% MW as reinforcement phase, thus confirming that marble wastes are a potential alternate material in developing AMCs.